The impacts of monetary policy shocks on the volatility of inflation, unemployment and exchange rate in Brazil - BARBOSA, Matheus Girola Macedo (2023)
This study evaluates the impacts of a contractionary monetary policy shock on inflation, unemployment rate, and exchange rate volatility in Brazil during the period of 2000-2020. These effects were analyzed through the estimation of impulse response functions and the decomposition of forecast error variance using a Bayesian Vector Autoregressive Model (BVAR). The results indicate that, following a monetary policy shock, inflation and unemployment volatility decrease by 15%, and exchange rate volatility decreases by 30%. These findings suggest that the reduction in volatility after the shock is attributed to increased confidence among agents in the commitment of the Central Bank of Brazil to achieving inflation targets.